2014
DOI: 10.1007/s40596-014-0189-5
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being in First Year Medical Students

Abstract: Medical schools should continue efforts to make counseling accessible. Conversations about counseling may help address the more negative attitudes of female students toward counseling, a finding which merits further investigation given that women typically have more positive attitudes toward counseling than men. Use of unhealthy coping strategies can be addressed in classes, clubs, and by advisors and mentors. Limitations of this study include that only first year medical students were surveyed and that it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In both of our samples, substance use could predict neither depression screening scores nor stress. While Erschens et al [ 36 ] emphasize that substance use increases the risk of burnout and Zanardelli and colleagues [ 32 ] reported that substance use was associated with lower well-being, Pickard et al [ 16 ] found no correlation between substance use and anxiety and depression. He interpreted this as being positive because the students were not using drugs as a coping strategy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both of our samples, substance use could predict neither depression screening scores nor stress. While Erschens et al [ 36 ] emphasize that substance use increases the risk of burnout and Zanardelli and colleagues [ 32 ] reported that substance use was associated with lower well-being, Pickard et al [ 16 ] found no correlation between substance use and anxiety and depression. He interpreted this as being positive because the students were not using drugs as a coping strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Wild et al [ 13 ] showed the effectiveness of an elective “relaxation techniques” course where students learned autogenic training and progressive muscle relaxation to conquer their stress. Medical schools should also offer easily accessible counseling for students in need of psychological care or support [ 32 ]. Additionally, universities should feel obliged to assess their curricula for especially stressful parts and try to implement necessary changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a single-site study, Al-Mateen et al [13] found that out of 64 third-year medical students, the majority experienced mental health concerns and psychological distress and developed symptoms from vicarious traumatization while in their psychiatry or surgery clerkships. In a study of 105 first-year medical students by Zanardelli et al [14], attributes such as gender appeared to shape attitudes toward counseling, and such attitudes were associated with well-being. In a study of 133 psychiatry residents who were in personal psychotherapy, Kovach et al [15] found that most reported their motivation to be improved self-awareness and self-reflection.…”
mentioning
confidence: 99%
“…In this issue of Academic Psychiatry, several papers examine health, well-being, and self-care of medical students and residents [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The set includes ten data-based reports.…”
mentioning
confidence: 99%